Efficacy and safety of imeglimin in Japanese patients with type 2 diabetes: A 24‐week, randomized, double‐blind, placebo‐controlled, dose‐ranging phase 2b trial. Issue 3 (13th January 2021) - Dubourg, Julie; Ueki, Kohjiro; Grouin, Jean‐Marie; Fouqueray, Pascale
Abstract: Aim: To assess the efficacy and safety of imeglimin monotherapy compared with placebo for 24 weeks in Japanese patients with type 2 diabetes (T2D). Materials and Methods: In this 24‐week, randomized, double‐blind, placebo‐controlled, parallel‐group, dose‐ranging, phase 2b clinical trial, Japanese adults (age ≥ 20 years) with T2D either treatment‐naïve or previously treated with one oral antidiabetes agent were eligible for participation. Patients were randomly assigned (1:1:1:1) to receive orally imeglimin 500, 1000 or 1500 mg, or placebo twice‐daily over a 24‐week period. The primary endpoint was the placebo‐adjusted change at week 24 in HbA1c. Safety outcomes were assessed in all patients who received at least one dose of study drug. Results: A total of 299 patients were randomized to receive double‐blind treatment with orally twice‐daily placebo (n = 75), imeglimin 500 mg (n = 75), 1000 mg (n = 74) or 1500 mg (n = 75). At week 24, imeglimin significantly decreased HbA1c (difference vs. placebo: imeglimin 500 mg −0.52% [95% CI: −0.77%, −0.27%], imeglimin 1000 mg −0.94% [95% CI: −1.19%, −0.68%], imeglimin 1500 mg −1.00% [95% CI: −1.26%, −0.75%]; P < .0001 for all). Treatment‐emergent adverse events were reported for 68.0%, 62.2%, 73.3% and 68.0% of patients receiving imeglimin 500, 1000 or 1500 mg and placebo, respectively. A small increase in gastrointestinal adverse effects (e.g. diarrhoea) occurred with the 1500 mg dose level. Hypoglycaemia was balanced among groups. Conclusions: Imeglimin as monotherapy in Japanese patients with T2D was well tolerated and significantly improved glycaemic control with no significant increase in hypoglycaemic events versus placebo. Given the marginal increase in efficacy with the 1500 versus 1000 mg dose (along with the potential for gastrointestinal tolerability issues), a dose of 1000 mg twice‐daily was selected for subsequent phase 3 studies.